2021
DOI: 10.3389/fnut.2021.733951
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Food Supplement Consumption in Polish Population of Adults

Abstract: Introduction: In recent years, there has been a great interest in food supplements. However the use of food supplements can be associated with the risk of excessive intake of vitamins or minerals which may have adverse health effects.Objective: Assessment of food supplement consumption in the adult population in Poland.Materials and Methods: The study was conducted on 1,831 adults (913 men, 918 women) from which 178 (59 men, 119 women) food supplement users were selected. The consumption of food supplements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
(49 reference statements)
1
19
0
Order By: Relevance
“…The BMI of the girls was equal to 18.93 kg/m 2 and that of the boys was equal to 19.03 kg/m 2 . Another report showed that in Polish children aged 10–13 the average BMI was slightly higher and equal to 19.6 kg/m 2 (B—19.9 kg/m 2 ; G—19.3 kg/m 2 ) [ 46 ]. The global BMI in children was also similar: it was equal to 18.60 kg/m 2 for girls and 18.50 kg/m 2 for boys [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The BMI of the girls was equal to 18.93 kg/m 2 and that of the boys was equal to 19.03 kg/m 2 . Another report showed that in Polish children aged 10–13 the average BMI was slightly higher and equal to 19.6 kg/m 2 (B—19.9 kg/m 2 ; G—19.3 kg/m 2 ) [ 46 ]. The global BMI in children was also similar: it was equal to 18.60 kg/m 2 for girls and 18.50 kg/m 2 for boys [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…?”), and the point in time when such information was collected. For instance, before the COVID-19 pandemic (i.e., March 2020 [ 6 ]), the percentage of those who used a DS during the last 12 months prior to their questioning was ~10% in both Spain [ 7 ] and Poland [ 8 ], but ~65% in Lithuania [ 9 ]. However, after COVID-19 was established as a pandemic, those percentages increased to 21% [ 10 ], ≥48% (“at least once in lifetime usage”) [ 11 ], and ~80% [ 9 ] respectively, indicating that COVID-19 might have played an impactful role.…”
Section: Introductionmentioning
confidence: 99%
“…Eating fish can reduce the incidence of cardiovascular disease but eating fried fish can increase the risk of cardiovascular events [ 36 , 37 ]. In Poland, it is particularly important to include fish in food-based dietary guidelines due to very low consumption in this country [ 27 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poles often eat sandwiches, especially for breakfast; a frequent addition to sandwiches are cold cuts and sausages. This can cause a higher consumption of processed meat [ 38 , 49 ]. In British studies from 2008 to 2019, the consumption of red and processed meat was similar; in 2018/2019 it was 34.7 and 36.1 g/person/day, respectively [ 44 ].…”
Section: Discussionmentioning
confidence: 99%